1998
DOI: 10.1016/s0022-5347(01)63986-7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Mk-801 on Bladder Overactivity in Rats With Cerebral Infarction

Abstract: Results in urethane anesthetized rats indicate that NMDA glutamatergic transmission is important in the overactivity of the bladder following a cerebral infarction. This model is useful in studying the neurogenic voiding dysfunction observed in patients with cerebrovascular disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(12 citation statements)
references
References 23 publications
1
11
0
Order By: Relevance
“…an increase in ICI, in urethane-anaesthetized rats, suggesting that NO has excitatory and inhibitory mechanisms, and that the excitatory mechanisms controlling bladder function are unmasked by urethane anaesthesia. These responses were consistent with the findings that MK-801, a N-methyl-D -aspartate (NMDA) receptor antagonist, decreased the BC in awake rats but increased the BC in urethaneanaesthetized rats [11,12]. The activation of NMDA receptors in the CNS initiates an influx of Ca 2 + , inducing Ca 2 + -dependent intracellular processes, while NOS is a Ca 2 + /calmodulindependent enzyme that is stimulated by the activation of NMDA receptors [13].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…an increase in ICI, in urethane-anaesthetized rats, suggesting that NO has excitatory and inhibitory mechanisms, and that the excitatory mechanisms controlling bladder function are unmasked by urethane anaesthesia. These responses were consistent with the findings that MK-801, a N-methyl-D -aspartate (NMDA) receptor antagonist, decreased the BC in awake rats but increased the BC in urethaneanaesthetized rats [11,12]. The activation of NMDA receptors in the CNS initiates an influx of Ca 2 + , inducing Ca 2 + -dependent intracellular processes, while NOS is a Ca 2 + /calmodulindependent enzyme that is stimulated by the activation of NMDA receptors [13].…”
Section: Discussionsupporting
confidence: 87%
“…It was proposed that two glutamatergic pathways regulate bladder activity. The first is an inhibitory pathway that originates from the forebrain, and the second is an excitatory pathway located at more caudal sites, possibly in the brainstem or in the spinal cord [12,16]. In the present study, i.c.v.…”
Section: Discussionmentioning
confidence: 95%
“…It has been speculated that two glutamatergic pathways regulate bladder activity. The first is an inhibitory pathway that originates from the forebrain and the second is an excitatory pathway located at more caudal sites, possibly in the brainstem or in the spinal cord 28 . It seems likely that activation of NMDA receptor‐linked NOS in the spinal cord and the brain is involved in the micturition reflex in normal and pathophysiological conditions.…”
Section: Central Role Of No In the Regulation Of The Lower Urinarymentioning
confidence: 99%
“…Some studies focusing on glutamatergic receptors in relation to micturition re ex (16, 18-20, 23, 33-35) have found that at least two glutamatergic systems in the brain are involved in the control of the micturition re ex pathway. One glutamatergic system, which has a low sensitivity to dizocilpine, originates in the brain stem and mediates excitatory control of voiding (19,34). The other system, which is more sensitive to dizocilpine, originates in the forebrain and activates an inhibitory mechanism that controls bladder capacity.…”
Section: Therapeutic Potential Of Central Dopaminergic and Gabaergic mentioning
confidence: 99%